(untitled) (Minerva. Revista de Filología Clásica, 2019)
This paper deals with the diffusion that the couple formed by Isis and Sarapis reached in the Greek and Roman world, with the nature of their cult and the causes of its diffusion. The authress tries to proof that the incubatio was practised in their temples and that the therapeutical powers attributed to these two deities were a decisive factor fot their spread and universalization.